(untitled) (New York, NY, 2000)
The book provides basic knowledge on solar system including the sun, earth, the moon and other planets each part of the book has explore activity and material that help to sold the problem rasing in the activity part
Keywords: Solar system,Hệ mặt trời; Study and teaching (Elementary),Dạy và học (cơ bản)